2006
DOI: 10.1302/0301-620x.88b2.16923
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three methods of wound closure following arthroplasty

Abstract: We carried out a blinded prospective randomised controlled trial comparing 2-octylcyanoacrylate (OCA), subcuticular suture (monocryl) and skin staples for skin closure following total hip and total knee arthroplasty. We included 102 hip replacements and 85 of the knee.OCA was associated with less wound discharge in the first 24 hours for both the hip and the knee. However, with total knee replacement there was a trend for a more prolonged wound discharge with OCA. With total hip replacement there was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
213
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(219 citation statements)
references
References 35 publications
2
213
4
Order By: Relevance
“…Many studies have previously compared wound closure techniques in TKA [2,3,6,[15][16][17][18]. Results have been highly variable and currently there is no consensus on a superior closure method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have previously compared wound closure techniques in TKA [2,3,6,[15][16][17][18]. Results have been highly variable and currently there is no consensus on a superior closure method.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have compared different closure techniques in TKA [2,3,6,[15][16][17][18]. From the perspective of wound complications, one recent meta-analysis by Smith et al showed that staple closure resulted in increased rates of infection after both hip and knee arthroplasty in comparison to running subcuticular [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of prospective studies revealed inconsistent results, even among those comparing procedures at the hip [3,7,18,19,21]. A meta-analysis of several studies showed three times higher risk of infection with staples, but according to the authors, only ''one study met acceptable methodologic criteria'' [20].…”
Section: Discussionmentioning
confidence: 99%
“…Initially this decision was guided solely by physician preference; however, as concerns about cost, poor wound outcomes, and patient satisfaction have become increasingly important, attention has been focused on demonstrating a clear benefit of one method over the other to guide practice [3,7,9,[18][19][20][21]. No clear advantage between sutures or staples has been demonstrated, and authors have attempted to show the advantages of each method.…”
Section: Introductionmentioning
confidence: 99%